Moisture curable silicon polyolefin polymers and methods
The existing polyolefin material curing technology is solved by melt blending of ethylene-SiH polymer with monoketone additives and triarylborane at a temperature of 80°C to 200°C and moisture curing in the presence of moisture. The problems of high demand, high cost and poor hydrolysis have achieved efficient curing and improved stability at ambient temperature.
Patent Information
- Application Number
- CN202380042571.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-22
- Publication Date
- 2025-01-03
AI Technical Summary
The curing technology of existing polyolefin materials has problems such as high temperature demand, high cost, many side reactions, and poor hydrolysis. In particular, the high cost of Pt-based catalysts and the moisture sensitivity of alkoxysilanes limit the application of the material.
The melt blending of ethylene-SiH polymer at a temperature of 80°C to 200°C with a monoketo additive and triarylborane to form a functionalized ethylene-Si polymer and wetted with a curing catalyst in the presence of moisture. Curing to form a crosslinked ethylene-Si polymer.
It realizes curing at ambient temperature, reduces costs, reduces side reactions, improves hydrolysis stability and storage stability, and maintains good curing kinetics under high temperature and high humidity conditions.
Smart Images

Figure BDA0005150475620000021 
Figure BDA0005150475620000071 
Figure BDA0005150475620000081
Abstract
Description
[0001] Curing of polyolefin materials is usually accomplished by: a) peroxide curing; b) platinum (Pt) catalyzed hydrosilylation when silicon hydride (SiH) or vinyl groups (C=C) are available; or c) moisture curing in the presence of a condensation catalyst when hydrolyzable groups such as alkoxysilane (-Si(OR)3) or hydride silane (-SiHR2) are available. Both a) and b) require high temperatures to initiate the curing process. Due to the high cost of Pt-based catalysts, the use of b is not recommended. In c), alkoxysilanes are usually installed on polyolefins via free radical methods, which are carried out after polymerization and are inevitably accompanied by chain scission and curing of the polymer backbone. Alternatively, alkoxysilane-functionalized polyolefins are synthesized by copolymerization of ethylene and unsaturated silanes (e.g., vinyltrimethoxysilane), which limits the material selection to mainly low-density polyethylene (LDPE). At the same time, the high sensitivity of alkoxysilanes to moisture requires a drying step to maintain low moisture content in the ingredients and prevent premature crosslinking. Compared to alkoxysilanes, the SiH groups on the olefin / silane interpolymers exhibit higher hydrolytic stability, which provides improved storage stability but at the same time results in slow cure kinetics, even when exposed to high temperatures and humidity levels.
[0002] Therefore, the art recognizes that there is a need to design new curing reactions for olefin-based polymers that are effective and economically viable. There is also a need for reactions that can install easily hydrolyzable groups onto a wide range of polyolefin materials with little or no side reactions, and these hydrolyzable groups provide the ability to cure functionalized polyolefins at ambient temperature (room temperature). Summary of the invention
[0003] The present disclosure provides a method. In one embodiment, the method includes performing a first melt blending of a first composition at a temperature of 80°C to 200°C. The first composition consists of (i) an ethylene-SiH polymer, (ii) a coagent as a monoketone, and (iii) triarylborane. The method includes forming a functionalized ethylene-Si polymer. The method also includes performing a second melt blending of a second composition at a temperature of 80°C to 200°C. The second composition consists of (iv) a functionalized ethylene-Si polymer and (v) a curing catalyst. The method includes moisture curing the second composition and forming a crosslinked ethylene-Si polymer.
[0004] The present disclosure provides a composition. In one embodiment, the composition comprises a functionalized ethylene-Si polymer having structure (1)
[0005] Structure (1)
[0006]
[0007] wherein n is an integer from 4 to 6. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 is a graph showing the DMA of IE2 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 eq. acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured at 20°C, 50% RH. The percentage next to the curve indicates the gel content.
[0009] Figure 2 is a graph showing the FTIR of ethylene-SiH polymer and IE2 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 eq acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) before and after 5 days of moisture curing at 20°C, 50% RH.
[0010] Figure 3 is a graph showing the DMA of IE3 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 eq acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured at 25°C, 16% to 25% RH.
[0011] Figure 4 is a graph showing the DMA of IE4 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 eq acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured at 50°C, 6% to 9% RH.
[0012] Figure 5 is a graph showing the DMA of IE5 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 eq. acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured at 21°C, 1% RH. The percentage next to the curve represents the gel content.
[0013] Figure 6 is a graph showing the DMA of IE6 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 equivalent of acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured in a water bath at 50° C. The percentage next to the curve represents the gel content.
[0014] Figure 7is a graph showing the DMA of IE7 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 eq. acetophenone to SiH, 500 ppm FAB, 100 ppm DBSA) cured at 20°C, 50% RH. The percentage next to the curve indicates the gel content.
[0015] Figure 8 is a graph showing the DMA of IE8 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 eq. acetophenone to SiH, 500 ppm FAB, 2000 ppm DBSA) cured at 20°C, 50% RH. The percentage next to the curve indicates the gel content.
[0016] Fig. 9 is a graph showing the DMA of IE9 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1 eq. acetophenone to SiH, 50 ppm FAB, 500 ppm DBSA) cured at 20°C, 50% RH. The percentage next to the curve indicates the gel content.
[0017] Fig.10 is a graph showing DMA of IE10 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 0.5 eq. acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured at 20°C, 50% RH. The percentage next to the curve indicates the gel content.
[0018] Fig.11 is a graph showing the DMA of IE11 (1MI ethylene-SiH polymer, 3.5 wt% HDMS, 1.5 eq. acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured at 20°C, 50% RH. The percentage next to the curve indicates the gel content.
[0019] Fig.12 is a graph showing the DMA of IE12 (1MI ethylene-SiH polymer, 1.5 wt% HDMS, 1 equivalent of acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured at 20°C, 50% RH. The percentage next to the curve indicates the gel content.
[0020] Fig.13 is a graph showing the DMA of IE13 (18MI ethylene-SiH polymer, 3 wt% HDMS, 1 eq acetophenone to SiH, 500 ppm FAB, 500 ppm DBSA) cured at 20°C, 50% RH. The 1 week and 2 week data are overlaid. The percentage next to the curve represents the gel content.
[0021] Fig.14 is a graph showing the DMA of CS1 (1 MI ethylene-SiH polymer, 2.5 wt% ODMS, 1 eq acetophenone, 500 ppm FAB) cured at 25°C, 16% to 25% RH.
[0022] Fig.15 is a graph showing the DMA of CS2 (1 MI ethylene-SiH polymer, 3.5 wt% HDMS, 2000 ppm DBSA) cured at 20°C, 50% RH. The percentage next to the curve indicates the gel content.
[0023] Fig.16 is a graph showing the DMA of CS3 (1 MIPOE, 1.8 wt% DCP) at 180°C for 10 minutes.
[0024] definition
[0025] Any reference to the Periodic Table of the Elements is to the Periodic Table as published by CRC Press, Inc., 1990-1991. A group of elements in this table is referred to by a new notation for numbering the groups.
[0026] For purposes of U.S. patent practice, the contents of any referenced patent, patent application, or publication are incorporated by reference in their entirety (or their equivalent U.S. versions are so incorporated by reference), especially with respect to definitions (to the extent not inconsistent with any definitions specifically provided in this disclosure) and common general knowledge in the art.
[0027] Numerical ranges disclosed herein include all values from the lower limit to the upper limit, and include the lower limit and the upper limit. For ranges containing exact values (e.g., 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two exact values is included (e.g., the above ranges 1 to 7 include 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6, etc.).
[0028] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are based on weight and all test methods are current as of the filing date of this disclosure.
[0029] The term "composition" refers to a mixture of materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0030] The terms "comprising", "including", "having" and their derivatives are not intended to exclude the presence of any additional components, steps or procedures, whether or not these components, steps or procedures are specifically disclosed. For the avoidance of any doubt, unless stated to the contrary, all compositions claimed by using the term "comprising" may include any additional additives, adjuvants or compounds, whether in polymeric form or otherwise. In contrast, the term "consisting essentially of excludes any other components, steps or procedures (except those that are not essential to operability) from the scope of any subsequent statements. The term "consisting of" excludes any components, steps or procedures that are not specifically described or listed. Unless otherwise stated, the term "or" refers to the listed members individually and in any combination. The use of the singular includes the use of the plural, and vice versa.
[0031] "Dalton" is a unit of polymer molecular weight, equivalent to the atomic mass unit, abbreviated as "Da" or "kDa" (kilodalton).
[0032] "Ethylene-based polymers" or "ethylene polymers" are polymers that contain a majority amount of polymerized ethylene, based on the weight of the polymer, and optionally may contain at least one comonomer. Ethylene-based polymers typically contain at least 50 mole percent (mol%) units derived from ethylene (based on the total amount of polymerizable monomers).
[0033] A "hydrocarbon" (or "hydrocarbyl" or "hydrocarbyl group") is a compound containing only hydrogen and carbon atoms.
[0034] As used herein, the term "heterohydrocarbon" ("heterohydrocarbon" or "heterohydrocarbon group") and similar terms refer to the corresponding hydrocarbon in which at least one carbon atom is replaced by a heteroatom group (eg, Si, O, N or P).
[0035] The term "substituted hydrocarbon" (or "substituted hydrocarbyl" or "substituted hydrocarbyl group") refers to a hydrocarbon in which one or more hydrogen atoms are independently replaced by a heteroatom group. The term "substituted heterohydrocarbyl" ("substituted heterohydrocarbyl" or "substituted heterohydrocarbyl group") and similar terms as used herein refer to the corresponding heterohydrocarbyl in which one or more hydrogen atoms are independently replaced by a heteroatom group.
[0036] "Interpolymers" are polymers prepared by polymerizing at least two different types of monomers. The generic term interpolymer thus includes copolymers (employed to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.
[0037] "Olefin-based polymers" or "polyolefins" are polymers containing a majority mole % of polymerized olefin monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin-based polymers include ethylene-based polymers and propylene-based polymers. Representative polyolefins include polyethylene, polypropylene, polybutene, polyisoprene, and various interpolymers thereof.
[0038] "Polymer" is a polymeric compound prepared by polymerizing monomers (whether of the same type or different types). Therefore, the general term polymer encompasses the term "homopolymer" (used to refer to polymers prepared from only one type of monomer, it should be understood that trace impurities can be incorporated into the polymer structure) and the term "interpolymer" as defined below. Trace impurities (e.g., catalyst residues) can be incorporated into the polymer and / or within the polymer. The general term also encompasses all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers as described above, respectively. It should be noted that although polymers are generally referred to as "made of" one or more specified monomers, "based on" a specified monomer or monomer type, "containing" a specified monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized residue of the specified monomer rather than unpolymerized substances. In general, polymers are referred to herein as "units" based on the polymerized form of the corresponding monomer.
[0039] "Propylene-based polymers" are polymers that contain a majority amount of polymerized propylene, based on the weight of the polymer, and optionally may include at least one comonomer. Propylene-based polymers typically contain at least 50 mole percent (mol%) units derived from propylene (based on the total amount of polymerizable monomers).
[0040] As used herein, the terms "thermally treating, thermal treatment" and similar terms refer to applying heat to a composition. Heat can be applied by conduction (e.g., heating coils), by convection (e.g., heat transfer through a fluid such as water or air), and / or by radiation (e.g., heat transfer using electromagnetic waves). Preferably, heat is applied by conduction or convection. Note that the temperature at which the thermal treatment is performed refers to the internal temperature of an oven or other device used to cure (or crosslink) the interpolymer.
[0041] Test Method
[0042] density Measured according to ASTM D792, Method B (g / cc or g / cm 3 ).
[0043] Differential Scanning Calorimetry (DSC) . Use differential scanning calorimetry (DSC) to measure Tm, Tc, Tg and crystallinity in ethylene-based polymer samples. Weigh about 5 mg to 8 mg of sample and place it in a DSC pan. Tighten the lid on the pan to ensure a closed atmosphere. Unless otherwise stated, place the sample pan in the DSC unit and then heat it to a temperature of 200°C at a rate of 10°C / min. Keep the sample at this temperature for three minutes. Then cool the sample to -90°C at a rate of 10°C / min and keep isothermally at this temperature for three minutes. Then heat the sample at a rate of 10°C / min until it is completely melted (second heating). Unless otherwise stated, the melting point (Tm) and glass transition temperature (Tg) of each polymer are determined by the second heating curve. Record the peak heat flow temperature of Tm.
[0044] Dynamic mechanical analysis Oscillatory rheological tests were performed on a strain-controlled rotational rheometer (ARES or ARES-G2, TA Instruments) using a rectangular torsion fixture geometry. Oscillations of small amplitudes within the linear viscoelastic range were applied at an angular frequency of 1 rad / s while rectangular samples (~2 mm thick) were heated at a ramp rate of 2 °C / min.
[0045] FTIR-ATR . Infrared spectra were collected on a Perkin ElmerFrontier Fourier transform infrared spectrometer (FT-IR) with an attenuated total reflectance (ATR) attachment (single bounce diamond / ZnSe). The sample was cut with scissors to expose the clean inner surface, then placed in the attachment and kept at a force of about 0.4 at the peak absorbance, and 4-16 scans were collected depending on the quality of the spectrum. Spectra were collected at least in triplicate to ensure representative sampling of the entire sample.
[0046] Gel content analysis A Soxhlet extraction apparatus was used following a procedure similar to that described in ASTM D2765. A known mass of sample (m0) was placed in a pre-weighed glass fiber sleeve (m t ) and extracted by boiling xylene (bp 136°C) under N2 for 15 hours. The thimble was then dried under vacuum at 50°C along with any sample residue. The final mass (m1) of the thimble and residual sample was measured and the gel content was calculated using the following equation.
[0047]
[0048] Gel Permeation Chromatography. For polymers 2-5 in the examples section, the chromatographic system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set to 160°C and the column compartment was set to 150°C. The columns were four AGILENT "Mixed A" 30cm 20 micron linear mixed bed columns. The chromatographic solvent was 1,2,4-trichlorobenzene containing 200ppm of butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters and the flow rate was 1.0 ml / min.
[0049] The GPC column set was calibrated with 21 narrow molecular weight distribution polystyrene standards, ranging in molecular weight from 580 to 8,400,000, and arranged in six "cocktail" mixtures, with at least ten times the interval between individual molecular weights. Standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, "0.025 grams" of polystyrene standards were prepared in 50 milliliters of solvent, and for molecular weights less than 1,000,000, "0.05 grams" of polystyrene standards were prepared in 50 milliliters of solvent. The polystyrene standards were dissolved at 80 degrees Celsius with gentle stirring for 30 minutes. The polystyrene standard peak molecular weight was converted to polyethylene molecular weight using equation 1 (EQ1) (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
[0050] M 聚乙烯 =A×(M 聚苯乙烯 ) B (EQ1),
[0051] Where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.
[0052] A fifth-order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents. A small adjustment was made to A
[0053] (approximately 0.375 to 0.445) to correct for column resolution and band broadening effects so that a linear homopolymer polyethylene standard is obtained at 120,000 Mw. Total plate counts for the GPC column set were performed with decane ("prepared as 0.04 g in 50 ml TCB" and dissolved for 20 minutes under slow stirring). Plate counts (Equation 2, EQ2) and symmetry (Equation 3, EQ3) were measured at 200 microliter injections according to the following equations:
[0054]
[0055] wherein RV is the retention volume in milliliters, Peak Width is in milliliters, Peak Maximum is the maximum height of the peak, and 1 / 2 Height is 1 / 2 the height of the Peak Maximum; and
[0056]
[0057] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum position of the peak, tenth height is 1 / 10 of the height of the peak maximum, and where post-peak refers to the tail of the peak with a retention volume later than the peak maximum, and where pre-peak refers to the front of the peak with a retention volume earlier than the peak maximum. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.
[0058] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml, and the solvent (containing 200 ppm BHT) was added to a septum-covered vial previously sparged with nitrogen by the PolymerChar high temperature autosampler. The samples were dissolved at 160 degrees Celsius for two hours under "low speed" shaking.
[0059] Based on the GPC results, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer, according to Equations 4-6, the PolymerChar GPCOne TM The software was used to calculate the Mn value of the baseline-subtracted IR chromatogram at each equidistant data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. (GPC) 、Mw (GPC) and Mz (GPC) Calculation. Equation 4-6 (EQ4-EQ6) is as follows:
[0060]
[0061] and
[0062]
[0063] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) for each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM calibrated)). It was then assumed that any changes in the time of the decane marker peak were related to linear changes in the flow rate (flow rate (effective)) for the entire run. In order to promote the highest accuracy of the RV measurement of the flow marker peak, the peak of the flow marker concentration chromatogram was fit to a quadratic equation using a least squares fitting procedure. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated according to Equation 7: Flow rate (effective) = flow rate (nominal) * (RV (FM calibration) / RV (FM sample)) (EQ7). By PolymerChar GPCOne TM The software completes the processing of the flow marker peaks. An acceptable flow rate correction is such that the effective flow rate should be within + / - 0.7% of the nominal flow rate.
[0064] For polymer 1 in the embodiment part, the chromatographic system consists of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment is set at 160°C and the column compartment is set at 150°C. These columns are an Agilent PLgel MIXED 7.5×50mm, 20μm linear mixed bed guard column followed by four Agilent PLgel MIXED-A 7.5×300mm, 20μm linear mixed bed columns. The chromatographic solvent is 1,2,4-trichlorobenzene (TCB) containing 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume used is 200 microliters, and the flow rate is 1.0 ml / min.
[0065] Agilent EasiCal polystyrene standards (EasiCal PS-1 and EasiCal PS-2) were used to calibrate the GPC column set. Each EasiCal system consists of two different scrapers supporting a mixture of 5 polymer standards (approximately 5 mg) to obtain 20 molecular weight points in the range of approximately 580 g / mole to 6,570,000 g / mole. A single scraper was added to a vial covered with a septum, sealed and loaded into the PolymerChar autosampler. 8 mL of solvent was added to each vial using the PolymerChar instrument control software, and the standards were dissolved at 160 ° C for 15 minutes under high-speed shaking before being injected into the chromatography system. Equation 7 was used to convert the polystyrene standard peak molecular weight into polyethylene molecular weight (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
[0066] M 聚乙烯 =A×(M 聚乙烯 ) B (EQ1), where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.
[0067] A third-order polynomial was used to fit the corresponding polyethylene equivalent calibration points. A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects so that a linear low density polyethylene standard was obtained at 120,000 Mw. Total plate counts for the GPC column set were performed with decane (3% v / v TCB introduced by a micro pump). Plate counts (Equation 2) and symmetry (Equation 3) were measured at 200 microliter injections according to the following equations:
[0068] wherein RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, and 1 / 2 height is 1 / 2 the height of peak maximum; and
[0069] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum peak position, tenth height is 1 / 10 the height of the peak maximum, and where post-peak refers to the tail of the peak at a later retention volume than the peak maximum, and where pre-peak refers to the front of the peak at an earlier retention volume than the peak maximum. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.
[0070] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml and the solvent (containing 200 ppm BHT) was added to the septum-capped vials by the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for two hours with high speed shaking.
[0071] Based on the GPC results, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer, according to Equations 4-6, the PolymerChar GPCOne TM The software was used to calculate the Mn value of the baseline-subtracted IR chromatogram at each equidistant data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. (GPC) 、Mw (GPC) and Mz (GPC) Calculation of. Equation 4-6 is as follows:
[0072]
[0073] and
[0074]
[0075] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) for each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM calibrated)). It was then assumed that any changes in the time of the decane marker peak were related to linear changes in the flow rate (flow rate (effective)) for the entire run. In order to promote the highest accuracy of the RV measurement of the flow marker peak, the peak of the flow marker concentration chromatogram was fit to a quadratic equation using a least squares fitting procedure. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated according to Equation 7: Flow rate (effective) = flow rate (nominal) * (RV (FM calibration) / RV (FM sample)) (EQ7). By PolymerChar GPCOne TM The software completes the processing of the flow marker peaks. An acceptable flow rate correction is such that the effective flow rate should be within + / - 0.7% of the nominal flow rate.
[0076] Melt indexThe melt index (or "I2") of ethylene-based polymers is measured according to ASTM D-1238 at 190°C / 2.16 kg (melt index I10 at 190°C / 10.0 kg). 10 Calculate I by the ratio of I2 10 / I2. The melt flow rate MFR of the propylene-based polymer is measured according to ASTM D-1238 at 230°C / 2.16kg.
[0077] Nuclear Magnetic Resonance (NMR) Characterization of Terpolymers .for 13 For C NMR experiments, samples were dissolved in tetrachloroethane-d2 (with or without 0.025M Cr(acac)3) in 10 mm NMR tubes. The concentration was approximately 300 mg / 2.8 mL. Each tube was then heated in a heating block set at 110 °C. The sample tubes were repeatedly vortexed and heated to obtain a uniformly flowing fluid. The data were collected on a BRUKER AVANCE 600 MHz spectrometer equipped with a 10 mm C / H DUAL cryogenic probe. 13 C NMR spectra. The following acquisition parameters were used: 60 s relaxation delay, 12.0 μs 90 degree pulse, 256 scans. The spectra were centered at 100 ppm and had a spectral width of 250 ppm. All measurements were performed at 110 °C without sample rotation. For the resonance peaks of the solvent, 13 The C NMR spectrum was located at "74.5 ppm". For samples containing Cr, data were collected at "7 sec relaxation delay" and 1024 scans.
[0078] for 1 For H NMR experiments, each sample was dissolved in tetrachloroethane-d2 in a 5 mm NMR tube. The concentration was approximately 100 mg / 1.8 mL. Each tube was then heated in a heating block set at 110 °C. The sample tubes were repeatedly vortexed and heated to obtain a uniformly flowing fluid. The spectra were acquired on a VARIAN 500 MHz spectrometer. 1 H NMR spectroscopy. Standard single pulse 1 H NMR experiments. The following acquisition parameters were used: 60 s relaxation delay, 16-32 scans. All measurements were performed at 110 °C without sample rotation. For the resonance peak of the solvent (residual protonated tetrachloroethane), 1 H NMR spectrum is located at "5.99 ppm". 1HNMR determines the polymerized SiH monomer content (wt%) in ethylene-SiH polymers. "Weight % SiH monomer" is calculated based on the integration of the SiMe proton resonance relative to the integration of the CH2 protons associated with the ethylene unit and the CH3 protons associated with the octene unit. "Weight % octene (or other α-olefin)" can be similarly determined by reference to the CH3 protons associated with the octene unit (or other α-olefin).
[0079] SiH conversion rate The SiH conversion was determined using FTIR-ATR. See FTIR-ATR Test Methods. The SiH conversion percentage (%) is described under the FTIR-ATR Test Methods. DETAILED DESCRIPTION
[0080] The present disclosure provides a method. In one embodiment, the method includes first melt blending a first composition consisting of (i) an ethylene-SiH polymer, (ii) an auxiliary agent as a monoketone, and (iii) a triaryl borane at a temperature of 80°C to 200°C, and forming a functionalized ethylene-Si polymer. The method also includes second melt blending a second composition consisting of (iv) a functionalized ethylene-SiH polymer and (v) a curing catalyst at a temperature of 80°C to 200°C, and then curing the second composition to form a cross-linked ethylene-Si polymer.
[0081] The method comprises first melt blending a first composition consisting of (i) an ethylene-SiH polymer, (ii) an auxiliary agent as a monoketone and (iii) a triarylborane at a temperature of 80° C. to 200° C. The ethylene-SiH polymer is composed of (1) an ethylene monomer, (2) 0.1 wt % to 3.9 wt % of a SiH comonomer and (3) an optional C3-C 12 As used herein, "SiH comonomer" (interchangeably referred to as "SiH") is a silane monomer of Formula 1:
[0082] (Formula 1)
[0083] A-(SiBC-O) x -Si-EFH
[0084] wherein A is an alkenyl group,
[0085] B is a hydrocarbon group or hydrogen,
[0086] C is a hydrocarbyl group or hydrogen, and
[0087] wherein B and C may be the same or different, and further B is a hydrocarbyl group, C is a hydrocarbyl group, and further B and C are the same;
[0088] H is hydrogen, and x ≥ 0;
[0089] E is a hydrocarbon group or hydrogen,
[0090] F is a hydrocarbyl group or hydrogen, E and F may be the same or different, and when E is a hydrocarbyl group, F is a hydrocarbyl group, and E and F may be the same hydrocarbyl group. Non-limiting examples of suitable SiH comonomers of Formula 1 include compounds s1) (allyl dimethyl silane), s2) (propylene dimethyl silane), s3) (butenyl dimethyl silane), s4) (hexenyl dimethyl silane), s5) (octenyl dimethyl silane), s6) (decenyl dimethyl silane), s7) norbornenyl ethyl dimethyl silane, s8) octahydrodimethylnaphthyl ethyl dimethyl silane, s9) vinyl tetramethyl disiloxane, s10) allyl tetramethyl disiloxane, s11) butenyl tetramethyl disiloxane, s12) hexenyl tetramethyl disiloxane, s13) octenyl tetramethyl disiloxane, s14) decenyl tetramethyl disiloxane, s15) norbornenyl ethyl tetramethyl disilane, s16) octahydrodimethylnaphthyl ethyl tetramethyl disiloxane, as follows:
[0091]
[0092]
[0093] In one embodiment, the SiH comonomer is selected from allyldimethylsilane, hexenyldimethylsilane, octenyldimethylsilane and hexenyltetramethyldisiloxane.
[0094] In one embodiment, the ethylene-SiH polymer is an ethylene / α-olefin / SiH terpolymer. The α-olefin in the ethylene / α-olefin / SiH comonomer terpolymer can be C3-C 12 α-olefin or C4-C8 α-olefin. Non-limiting examples of suitable α-olefins include propylene, butene, hexene, octene and ethylidene norbornene, for ethylene / propylene SiH terpolymer, ethylene / butene / SiH terpolymer, ethylene / hexene / SiH terpolymer, ethylene / octene / SiH terpolymer and ethylene / ethylidene norbornene / SiH terpolymer, respectively.
[0095] In one embodiment, the ethylene / α-olefin / SiH terpolymer is an ethylene / octene / SiH terpolymer. Non-limiting examples of suitable ethylene / octene / SiH terpolymers include ethylene / octene / hexenyldimethylsilane (HDMS) terpolymers, ethylene / octene / octenyldimethylsilane (ODMS) terpolymers, and combinations thereof.
[0096] In one embodiment, the ethylene / α-olefin / SiH terpolymer is an ethylene / octene / SiH terpolymer. The ethylene / octene / SiH terpolymer comprises 32 wt% to 35 wt% octene and 0.5 wt% to 5 wt% or 1.0 wt% to 3.5 wt% SiH comonomer, and has a density of 0.87 g / cc to 0.89 g / cc and a MI of 1 g / 10min to 18 g / 10min or 2 g / 10min to 12 g / 10min. Non-limiting examples of suitable ethylene / octene / SiH terpolymers include ethylene / octene / allyl dimethyl silane (ADMS) terpolymers, ethylene / octene / hexenyl dimethyl silane (HDMS) terpolymers, ethylene / octene / octenyl dimethyl silane (ODMS) terpolymers.
[0097] In one embodiment, the ethylene-SiH polymer is selected from the group consisting of ethylene / octene / HDMS terpolymers and ethylene / octene / ODMS terpolymers.
[0098] In one embodiment, the ethylene-SiH polymer is an ethylene / octene / HDMS terpolymer.
[0099] In one embodiment, the ethylene-SiH polymer is an ethylene / octene / ODMS terpolymer.
[0100] The first composition comprises (ii) an adjuvant that is a monoketone (interchangeably referred to as a "monoketone adjuvant"). As used herein, a "monoketone adjuvant" is a hydrocarbon containing a single carbonyl group. Non-limiting examples of suitable monoketone adjuvants include acetophenone, benzophenone, acetone, methyl ethyl ketone, and butanone. In one embodiment, the monoketone adjuvant is acetophenone.
[0101] The first composition comprises (iii) triarylborane. The three aryl groups may be the same or different. Each of the three aryl groups may independently include one, or two, or three, or four, or five substituents selected from hydrogen, chlorine, fluorine, trifluoromethyl groups and combinations thereof. Triarylborane is a Lewis acid catalyst and promotes the hydrosilylation reaction between the SiH monomer of the ethylene-SiH polymer and the carbonyl group of 1,3-dibenzoylpropane. Non-limiting examples of suitable triarylboranes include tris(pentafluorophenyl)borane (FAB), tris(3,5-bis(trifluoromethyl)phenyl)borane; bis(3,5-bis(trifluoromethyl)phenyl)(2,4,6-trifluorophenyl)borane; bis(3,5-bis(trifluoromethyl)phenyl)(2,5-bis(trifluoromethyl)phenyl)borane; bis(3,5-bis(trifluoromethyl)phenyl)(4-trifluoromethylphenyl)borane, bis(3,5-bis(trifluoromethyl)phenyl)(2,6-difluorophenyl)borane, tris(2,5-bis(trifluoromethyl)phenyl)borane, and combinations thereof.
[0102] (i) ethylene-SiH polymer, (ii) monoketone auxiliary agent and (iii) triarylborane are melt blended (or first melt blended) or otherwise mixed at a temperature and time sufficient to completely homogenize the mixture. The first melt blending is carried out by intermittent mixing or continuous mixing at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes. In the presence of triarylborane catalyst, the first melt blending initiates a hydrosilylation reaction between the Si-H portion of the ethylene-SiH polymer and the carbonyl group of the monoketone auxiliary agent, thereby grafting the monoketone auxiliary agent onto the ethylene-SiH polymer to form a functionalized ethylene-Si polymer. As used herein, "functionalized ethylene-Si polymer" is the reaction product between an ethylene-SiH polymer and a monoketone auxiliary, wherein the monoketone auxiliary is grafted or otherwise covalently bonded to the ethylene-SiH polymer at the silicon atom of the SiH moiety through a Si-OC- bond.
[0103] The functionalized ethylene-Si polymer has little or no crosslinking and has a gel content of 0% to less than 2.5%. In other words, the functionalized ethylene-Si polymer has a gel content of less than 1×10 6 Pa shear storage modulus (G') value.
[0104] In one embodiment, the crosslinked ethylene-Si polymer is the reaction product between an ethylene-SiH polymer and a monoketone adjuvant (acetophenone), whereby the acetophenone is grafted to the ethylene-SiH polymer to form the following structure (1):
[0105] Structure (1)
[0106]
[0107] in
[0108] Me is a methyl group (CH3), and
[0109] n is an integer of 4 to 6 (or 4, or 5, or 6).
[0110] The method comprises subjecting a second composition consisting of (iv) a functionalized ethylene-Si polymer and (v) a curing catalyst to a second melt blending at a temperature of 80°C to 200°C. As used herein, a "curing catalyst" is a catalyst that accelerates the curing of two or more olefin / silane interpolymer chains in the presence of moisture. 1 )(R 2)H) between the reaction. Examples of curing catalysts include metal alkoxides, metal carboxylates, metal sulfonates, aryl sulfonic acids and triarylboranes. Metal alkoxides are generally composed of M(OR) n It represents, wherein M is a metal, R is an alkyl group, and n≥1. In one embodiment, M is titanium (Ti) or tin (Sn).
[0111] Metal carboxylates are usually composed of M[OC(O)-R] m Represented by, where M is a metal, R is an alkyl group, and m ≥ 1, or by (R') n M[OC(O)-R] m It represents, wherein R' and R are each independently an alkyl group, M is a metal, n≥1 and m≥1. In one embodiment, M is Ti or Sn. In another embodiment, M is Sn.
[0112] Metal sulfonates are usually composed of M[OS(O)2R] n = , wherein M is a metal, R is a substituted or unsubstituted alkyl group, and n≥1. For example, one or more hydrogen atoms on the alkyl group may be substituted with a halogenated group such as F. In one embodiment, M is bismuth.
[0113] Aryl sulfonic acid comprises at least one aryl group and at least one sulfonic acid group. Examples of aryl sulfonic acid are represented by Ar-S(O)2-OH, where Ar is an aryl group comprising one or more alkyl groups. The aryl group can be bicyclic, tricyclic, etc. Examples of aryl sulfonic acid are described in International Publication WO2002 / 12355, which is incorporated herein by reference.
[0114] Non-limiting examples of suitable curing catalysts include dibutyltin dilaurate, tetrabutyltitanium oxide, dodecylbenzenesulfonic acid (DBSA), bismuth trifluorosulfonate, and combinations thereof.
[0115] In one embodiment, the curing catalyst is dodecylbenzenesulfonic acid (DBSA).
[0116] The components (iv) of the second composition, the functionalized ethylene-Si polymer and (v) the curing catalyst are melt blended (or second melt blended) or otherwise mixed at a temperature and time sufficient to completely homogenize the mixture. The second melt blending is carried out by intermittent mixing or continuous mixing at a temperature of 80° C. to 200° C., or 90° C. to 150° C., or 100° C. to 120° C. for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes.
[0117] In one embodiment, the method includes forming or otherwise shaping the second composition into an article (before the moisture curing step). Non-limiting forming procedures include pressing, rolling, molding, extruding, compressing, and combinations thereof to form non-limiting articles such as films, sheets, plates, pellets, annular structures, and combinations thereof.
[0118] After the second melt blending is completed, the second composition is wet-cured to form a cross-linked ethylene-Si polymer. As used herein, "wet-curing" refers to the curing or cross-linking of the second composition (after the second melt blending) when exposed to water. Water can be in the form of atmospheric moisture (moisture present in the air) or water in the form of a water bath. The speed and degree of wet curing or cross-linking are the amount of silane functional groups in the second composition, the properties exposed to water (e.g., immersed in a water bath, the relative humidity of the air, etc.), the duration of exposure and the function of the temperature. During wet curing, the Si-OC bond in the functionalized ethylene-SiH polymer is hydrolyzed in the presence of moisture (water, air humidity, steam) and a curing catalyst to form a silanol group. The silanol groups condense with each other in the presence of a curing catalyst to form a Si-O-Si bond, and the Si-O-Si bond bonds each chain of the ethylene-SiH polymer to each other or cross-links in other ways. As used herein, "crosslinked ethylene-Si polymer" is a moisture cure reaction product whereby Si-O-Si bonds crosslink or otherwise bond together individual polymer chains of the functionalized ethylene-SiH polymer to form a network structure of bonded polymer chains.
[0119] In one embodiment, moisture curing comprises exposing the second composition to air at a relative humidity (RH) of 10% to 70%, or 15% to 60% and a temperature of 10° C. to 60° C., or 10° C. to 50° C., or 10° C. to 25° C. for 24 to 336 hours. Moisture curing forms a crosslinked ethylene-Si polymer.
[0120] In one embodiment, moisture curing comprises immersing the second composition in a water bath at a temperature of 20°C to 90°C, or 20°C to 60°C, or 20°C to 50°C for 24 hours to 168 hours. Moisture curing forms a crosslinked ethylene-Si polymer.
[0121] In one embodiment, the crosslinked ethylene-Si polymer is a moisture-cured reaction product between (i) a functionalized ethylene-Si polymer having structure (1) and (ii) a curing catalyst DSBA, the reaction product forming a crosslinked ethylene-Si polymer having the following structure (2):
[0122] Structure (2)
[0123]
[0124] in
[0125] Me is a methyl group (CH3), and
[0126] n is an integer of 4 to 6 (or 4, or 5, or 6).
[0127] In one embodiment, the first melt blending and / or the second melt blending are performed by batch mixing in a batch mixer. For the first melt blending, (i) ethylene-SiH polymer, (ii) monoketone coagent and (iii) triarylborane are introduced into a batch mixer and melt blended or otherwise mixed at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes. Non-limiting examples of suitable batch mixers include BANBURY TM Mixer, BOLLING TM Mixer or HAAKE TM Mixer. Batch mixing to form a functionalized ethylene-Si polymer. In one embodiment, the monoketone adjuvant is acetophenone, and batch mixing to form a functionalized ethylene-Si polymer having structure (1).
[0128] In one embodiment, the second melt blending is performed by batch mixing in a batch mixer. For the second melt blending, (iv) the functionalized ethylene-Si polymer and (v) the curing catalyst are introduced into the batch mixer and melt blended or otherwise mixed at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes. Non-limiting examples of suitable batch mixers include BANBURY TM Mixer, BOLLING TM Mixer or HAAKE TM Mixer. Batch mixing forms a second composition which is then moisture cured to form a crosslinked ethylene-Si polymer having structure (2).
[0129] In one embodiment, the first melt blending and / or the second melt blending are performed by continuous mixing in an extruder. For the first melt blending, (i) ethylene-SiH polymer, (ii) monoketone coagent and (iii) triarylborane are introduced into an extruder and melt blended or otherwise mixed at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes to form a uniform composition. The extruder can be a continuous single screw extruder or a continuous twin screw extruder. Non-limiting examples of suitable extruders include FARREL TMContinuous mixer, COPERION TM Twin screw extruder or BUSS TM kneading continuous extruder. The homogeneous composition leaves the extruder die as an extrudate, which is a functionalized ethylene-Si polymer. In one embodiment, the monoketone adjuvant is acetophenone, and the homogeneous composition leaves the extruder die as an extrudate, which is a functionalized ethylene-Si polymer having structure (1).
[0130] In one embodiment, the second melt blending is carried out by continuous mixing in an extruder. For the second melt blending, (iv) functionalized ethylene-Si polymer and (v) curing catalyst are introduced into an extruder and melt blended or otherwise mixed at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes to form a uniform composition. The extruder can be a continuous single screw extruder or a continuous twin screw extruder. Non-limiting examples of suitable extruders include FARREL TM Continuous mixer, COPERION TM Twin screw extruder or BUSS TM The homogeneous composition leaves the outlet die of the extruder as an extrudate consisting of the second composition, which is subsequently moisture cured to form a crosslinked ethylene-Si polymer having structure (2).
[0131] In one embodiment, the method includes providing a first composition consisting of (i) an ethylene-SiH polymer, (ii) a monoketone auxiliary and (iii) a triaryl borane. The ethylene-SiH polymer contains Si atoms present in the SiH comonomer. The monoketone auxiliary contains a carbonyl moiety. As used herein, "carbonyl: SiH molar ratio" is the ratio of the molar number of carbonyl groups present in the monoketone auxiliary to the molar number of Si atoms present in the ethylene-SiH polymer. The method includes providing a first composition having components (i) to (iii) and having a carbonyl: SiH molar ratio of 0.25 to 2.5, or 0.5 to 2.0, or 0.50 to 1.5, performing a first melt blending on the first composition at a temperature of 80° C. to 200° C., and forming a functionalized ethylene-Si polymer. In one embodiment, the monoketone auxiliary is acetophenone, and the functionalized ethylene-Si polymer has structure (1). The functionalized ethylene-Si polymer (having structure (1)) has a gel content of 0%, or greater than 0% to less than 2.5%. The method also includes subjecting a second composition consisting of (iv) a functionalized ethylene-Si polymer (having structure (1) and a gel content of 0%, or greater than 0% to less than 2.5%) and (v) a curing catalyst to a second melt blending, followed by moisture curing of the second composition to form a cross-linked ethylene-Si polymer having structure (2).
[0132] In one embodiment, the method includes first melt blending a first composition comprising (i) 95 wt% to 98 wt% of an ethylene / α-olefin / SiH terpolymer, (ii) 1 wt% to 10 wt%, or 3 wt% to 8 wt% of a monoketone adjuvant acetophenone, (iii) 5 ppm to 5000 ppm, or 10 ppm to 100 ppm of a trialkylborane at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes, wherein the first composition has a carbonyl:SiH molar ratio of 0.25 to 2.5, or 0.5-2.0, or 0.5 to 1.5; and forming a functionalized ethylene Si-H polymer having structure (1) and a gel content of 0%, or greater than 0% to less than 2.5%. The method further comprises subjecting a second composition consisting of (iv) a functionalized ethylene-Si polymer and (v) a curing catalyst DBSA to a second melt blending, and moisture curing the second composition (after the second melt blending) to form a crosslinked ethylene-Si polymer having structure (2).
[0133] The present disclosure provides a composition. In one embodiment, the composition comprises a functionalized ethylene-Si polymer having structure (1)
[0134] Structure (1)
[0135]
[0136] in
[0137] Me is a methyl group (CH3), and
[0138] n is an integer of 4 to 6 (or 4, or 5, or 6).
[0139] The crosslinked ethylene-Si polymer having structure (1) has one, some or all of the following characteristics:
[0140] (i) a density of 0.86 g / cc to 0.88 g / cc, and / or
[0141] (ii) 3000 ppm to 7000 ppm silicon atoms, and / or
[0142] (iii) 1 ppm to 10 ppm of boron atoms.
[0143] Applicants have discovered a method for easily and predictably converting SiH groups to hydrolyzable groups, such as alkoxysilanes and silyl esters, by reacting the SiH moieties of ethylene-SiH polymers with carbonyl-containing coagents (e.g., monoketones, coagents) in the presence of a Lewis acid catalyst (e.g., triarylborane). This post-polymerization functionalization method is applicable not only to linear low density polyethylene (LLDPE), but also to low density polyethylene (LDPE) and high density polyethylene (HDPE). Further incorporation of a Bronsted acid catalyst (curing catalyst, such as DBSA) enables the resulting second composition to cure at ambient to moderate temperatures (20°C to 60°C) and below the melting point of the ethylene-SiH polymer and / or below the melting point of the second composition when exposed to (atmospheric) moisture. The ability of the present method to achieve ambient cure is unexpected and advantageous.
[0144] By way of example and not limitation, some embodiments of the present disclosure will now be described in detail in the following examples.
[0145] Example
[0146] 1. Materials
[0147] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 1 below.
[0148] Table 1 - Materials
[0149]
[0150] A. Synthesis and properties of polymers P1, P2, P3, P4 and P5
[0151] The ethylene / octene / silane copolymerization for producing polymer 1 (ethylene-SiH polymer) was carried out in a batch reactor designed for ethylene homopolymerization and copolymerization. The reactor was equipped with an electric heating tape and an internal cooling coil containing cooling glycol. Both the reactor and the heating / cooling system were controlled and monitored by a process computer. The bottom of the reactor was equipped with a dump valve, which emptied the reactor contents into a dump pot connected to the atmosphere. All chemicals and catalyst solutions used for polymerization were passed through a purification column before use. ISOPAR-E, 1-octene, ethylene and silane monomers were also passed through the column. Ultra-high purity grades of nitrogen (Airgas) and hydrogen (Airgas) were used. The catalyst mixture was prepared by mixing a scavenger (MMAO), an activator (bis(hydrogenated tallow alkyl) methylamine tetra(pentafluorophenyl) borate (1<->)) and a catalyst with an appropriate amount of toluene in an inert glove box to obtain a solution of the desired molar concentration. The solution was then diluted with ISOPAR-E or toluene to achieve the amount required for polymerization and aspirated into a syringe to transfer to a catalyst injection tank.
[0152] In a typical polymerization, ISOPAR-E and 1-octene are loaded into the reactor via separate flow meters. The silane monomer is then added via an injection tank input through an adjacent glove box. After the addition of solvent / comonomer, hydrogen is added (if necessary) while the reactor is heated to a polymerization set point of 120°C. Ethylene is then added to the reactor via a flow meter at the desired reaction temperature to maintain a predetermined reaction pressure set point. The catalyst solution is transferred to an injection tank via a syringe and then added to the reactor via a high pressure nitrogen stream after the reactor pressure set point is reached. The run timer is started upon injection of the catalyst, after which an exotherm and a decrease in reactor pressure are observed to indicate a successful run.
[0153] Ethylene was then added using a pressure controller to maintain the reaction pressure set point in the reactor. The polymerization was run for a set time or until ethylene was absorbed, after which the agitator was stopped and the bottom dump valve was opened to empty the reactor contents into a dump tank. The tank contents were poured into a tray placed in a fume hood and the solvent was allowed to evaporate overnight. The tray containing the remaining polymer was then transferred to a vacuum oven and heated to 100°C under reduced pressure to remove any residual solvent. After cooling to ambient temperature, the polymer was weighed to obtain the yield / efficiency, transferred to a container for storage and submitted for analytical testing.
[0154] Interpolymers Polymers 2-5 (ethylene-SiH polymers) were each prepared in a one-gallon polymerization reactor that was full of liquid and operated under steady-state conditions. Detailed synthesis information is provided for several of the listed examples. The solvent was ISOPAR-E supplied by ExxonMobil Chemical Company. 5-Hexenyldimethylsilane (HDMS) supplied by Gelest was used as a terpolymer monomer and purified via AZ-300 alumina supplied by UOP Honeywell before use. HDMS was fed to the reactor as a 22 wt% ISOPAR-E solution. The reactor temperature was measured at or near the reactor outlet. The interpolymers were separated and pelletized. The polymerization conditions are listed in Tables 1C-1E, and the catalyst is shown in Table 1B. The polymer properties of each ethylene-SiH polymer P1, P2, P3, P4, P5 are shown in Tables 2A and 2B.
[0155] Table 1A: Polymerization conditions for producing polymer 1
[0156]
[0157] Table 1B: Catalysts and co-catalysts
[0158]
[0159] Table 1C: Polymerization conditions for producing polymers 2-5
[0160]
[0161] Table 1D: Catalyst feed flow rates and efficiencies for production of polymers 2-5
[0162]
[0163] *"ppm" amounts are based on the weight of the corresponding catalyst feed solution.
[0164] Table 1E: Cocatalyst Feed Flow Rates for Production of Polymers 2-5
[0165]
[0166] *The "ppm" amounts are based on the weight of the co-catalyst feed solution. **The "ppm" amounts of Al are based on the weight of the co-catalyst feed solution.
[0167] Table 2A: Polymer Properties
[0168]
[0169] *Mole % silane is based on the total moles of monomers in the polymer and is determined by 1H NMR
[0170] **Silane weight % is calculated by mole % and is based on the weight of the interpolymer.
[0171] Table 2B: Polymer Properties (Conventional GPC)
[0172] Resin Mn(kg / mol) Mw(kg / mol) Mw / Mn Polymer 1 47 111 2.4 Polymer 2 45 100 2.2 Polymer 3 52 112 2.2 Polymer 4 49 108 2.2 Polymer 5 25 52 2.1
[0173] B. Melt Blending
[0174] At 100°C, moisture-curable materials (IE1-13, CS1-2): (i) ethylene-SiH polymer, (ii) monoketone coagent, and (iii) FAB solution in toluene (75 mg / mL) (first composition) were fed sequentially into a torque rheometer (Haake Flow Meter) equipped with a 20 mL or 50 mL bowl and two roller rotors. TM Rheomix QC Lab Mixers or HAAKE TM Rheomix OS LabMixers, Thermal Scientific). After adding each component, the sample (first composition) was mixed at 60rpm for 1 minute (min) (first melt blending). The final blend was mixed for another 4 minutes (first melt blending). The hot melt was then taken out from the blender to obtain a functionalized ethylene-Si polymer having structure (1). The SiH conversion of the functionalized Si-H polymer was analyzed using FTIR-ATR. The second composition was prepared in the following manner: compounding (i) functionalized ethylene-Si polymer (having structure (1)), feeding it into a 20mL bowl of a torque rheometer and melting it at 100°C, and mixing it at 60rpm for 1 minute (second melt blending). Subsequently, a curing catalyst DBSA was added, and the blend was mixed for 5 minutes (second melt blending) to obtain a second composition. The second composition was compression molded at 90°C under a force of 20,000lbs for 4 minutes to form a torsion bar (1.7mm thick).
[0175] Heat-curable material (CS3): POE pellets (98.2 wt%) were mixed with a curing additive (1.8 wt% dicumyl peroxide) in a sealable glass jar. The soaking process was carried out by shaking and 4 hours of imbibition until no liquid residue adhering to the glass jar was visible to the naked eye. Afterwards, the imbibed sample was melt blended in a RSI RS5000, RHEOMIX 600 mixer with a CAM paddle at 100°C / 30rpm for six minutes. The hot sample was cooled at 20,000psi for four minutes in a Carver press (cold platen) to make a "pancake sample" for further testing. The final sample was compression molded at 100°C for 5 minutes at a force of 20,000lbs to form a plate (1.7mm thick).
[0176] C. Moisture curing
[0177] Moisture Curing (IE1-13, CS1-2): The molded moisture-curable material (1.7 mm thick torsion bar composed of the second composition) was subjected to different moisture curing conditions: 1) 20°C, 50% relative humidity (RH); 2) 25°C, 16% to 25% RH; 3) 50°C, 6% to 9% RH; 4) 50°C water bath;
[0178] 5) 1% RH. Heat curing (CS3): The molded heat curable material was heated at 180°C for 10 minutes in a compression molding machine.
[0179] The amounts and ratios of components (i), (ii), (iii), (iv) and (v) in the resulting formulations CS1-CS3 and IE1-IE15 are provided in Table 3 below.
[0180]
[0181] Table 4
[0182]
[0183] Figure 1 The temperature dependence of the storage modulus (G') of the composition using acetophenone (IE2) as an auxiliary agent before and after moisture curing at 20°C, 50% RH is shown. The G' of the material increases with time, and the high temperature plateau of the storage modulus indicates the formation of a cross-linked three-dimensional network after moisture curing, which is further confirmed by the 97% gel content. FTIR-ATR shows that by mixing ethylene-SiH polymer and acetophenone in the presence of FAB, the SiH in the functionalized ethylene-Si polymer is quantitatively converted to alkoxysilane, as shown at about 890 cm -1 The disappearance of the SiH peak at about 1100 cm -1 The appearance of SiOC peak at Figure 2 ). At about 960cm -1 The new peak at 960 cm-1 can also be assigned to the resulting silyl ether structure. After 5 days of exposure to moisture (moisture curing), the peak at 960 cm-1 -1 and 1100cm -1 At the same time, the peak associated with Si-O-Si appears at about 1060 cm -1 , indicating that siloxane crosslinks were formed under ambient conditions.
[0184] Figures 3 to 13The temperature dependence of the storage modulus (G') of different compositions (IE3-13) using acetophenone as an adjuvant before and after moisture curing under various conditions is shown. In most cases, the G' of the materials increases with time as the samples cure. The positive slope of the plateau storage modulus indicates that these materials have formed a rubbery network. Although the cure of IE7 containing 500 ppm DBSA is slower ( Figure 7 ), but IE7 still reached 34% gel content after 2 weeks.
[0185] Fig.14 The temperature dependence of the storage modulus (G') of a composition without DBSA (CS1) after exposure to moisture curing conditions is shown. Little change was observed after 6 days, indicating that the use of a Bronsted acid (curing catalyst) as a moisture curing catalyst is necessary.
[0186] Fig.15 The temperature dependence of the storage modulus (G') of a composition containing only SiH-POE and DBSA (CS2) is shown. Little change was observed after 7 days, indicating that conversion of SiH to silyl ether or silyl ester is necessary for moisture curing to occur under ambient conditions.
[0187] Dicumyl peroxide (DCP) is commonly used to cure polyolefin elastomers via a free radical mechanism. Fig.16 The temperature dependence of the storage modulus (G') of the peroxide-cured POE (CS3) is shown, with the plateau G' being much lower than that of the moisture-cured material due to the lower degree of chemical cross-linking.
[0188] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.
Claims
1. A method, comprising: The first composition is first melt-blended at a temperature of 80° C. to 200° C., wherein the first composition comprises (i) ethylene-SiH polymer, (ii) as an auxiliary agent for monoketones, and (iii) triarylborane; forming a functionalized ethylene-Si polymer; A second composition is melt blended at a temperature of 80°C to 200°C, wherein the second composition comprises (iv) said functionalized ethylene-Si polymer, and (v) a curing catalyst; moisture curing the second composition; as well as A cross-linked ethylene-Si polymer is formed.
2. The method according to claim 1, comprising: providing a first composition having a carbonyl:SiH molar ratio of 0.25 to 2.5; and Functionalized ethylene-SiH polymers are formed having a gel content of 0% to less than 2.5%.
3. The method according to any one of claims 1 to 2, comprising: A first composition is provided, the first composition comprising (i) 95 to 98 wt. % of an ethylene / α-olefin / -SiH terpolymer, (ii) 2 to 5 wt. % of the auxiliary agent, (iii) 5 ppm to 500 ppm of the trialkylborane.
4. The method of any one of claims 1 to 3, comprising forming a functionalized ethylene-SiH polymer having Si-OC bonds.
5. The method according to any one of claims 1 to 4, comprising forming a functionalized ethylene-SiH polymer having structure (1) Structure (1) wherein n is an integer from 4 to 6.
6. The method according to any one of claims 1 to 5, comprising: A second composition is provided, the second composition comprising (iv) 95 to 98 wt% of a functionalized ethylene / α-olefin / -SiH terpolymer, and (v) 100 ppm to 2000 ppm of said curing catalyst; moisture curing the second composition; as well as A cross-linked ethylene-Si polymer having Si-O-Si bonds is formed.
7. The method according to claim 6, comprising forming a cross-linked ethylene-SiH polymer having structure (2) Structure (2) wherein n is an integer from 4 to 6.
8. A composition comprising: Functionalized ethylene-Si polymer having structure (1) Structure (1) wherein n is an integer from 4 to 6.
9. The composition of claim 8, wherein the composition has a density of 0.86 g / cc to 0.88 g / cc.
10. The composition according to any one of claims 8 to 9, comprising 3000 ppm to 7000 ppm of silicon atoms.
11. The composition according to any one of claims 8 to 10, comprising 1 ppm to 10 ppm of boron atoms.
